Pengaruh Ukuran Partikel dan Pencucian terhadap Degradasi in Sacco beberapa Bahan Pakan pada Sapi Peranakan Friesian Hostein = Effect of Particle Size and Rinsing Technique on in sacco Degradation of Some Feeds Stuff in - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This experiment was conducted to determine the effect of particle size and bags rinsing technique on in sacco degradation of rice straw, corn stover, peanut vines, coconut oil meal and palm oil meal. Two female rumen fistulated Friesian Holstein grade cattle, non pregnant and dry were used in this experiment. In sacco method was applied to evaluate degradation by incubating the sample of feed rice straw, corn stover, peanut vines at 4,8,16,24,48 and 72 hours and at 2,4,8,16,24 and 48 hours to coconut oil meal and palm oil meal. 2 mm and < 2 mm of particle size were used in this experiment. Bags Than machine or hand rinsing bags used for CP degradation. Fraction of feeds which disappear were described by the expression (Orskov and McDonald, 1979): td = a + b (1-exfP). DT value were determine by equation DT=a+{(b.c)/(c+0,06)j. Statistical design was a complete randomized block with a 2x2x5 factorial arrangement of particle size, rinsing technique and feeds. The results showed particle size < 2 mm was no significant (P>0,05) CP degradability than particle 2 mm (52,4% vs 51,7%). Between forage species with particle size 2 mm or < 2 mm found different significant (P0,01) on CP degradation. Higher degradability was found coconut oil meal and lower on rice straw. The study as concluded that particle size < 2 mm had influence on CP disappear and degradation of feeds than particle size 2 mm. Bags rinsing technique were by machine or hand no influence on CP disappear and degradation of feeds.